2020
DOI: 10.1017/s136898002000186x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and regional variations of coexistence of child stunting and maternal overweight or obesity in Myanmar

Abstract: Objective: The current study aimed to investigate double burden of malnutrition within households at the national and subnational levels and to identify its association with sociodemographic factors in Myanmar. Design: All the variables were extracted from children’s file of the Myanmar Demographic and Health Survey 2015–2016. Children under five were identified as stunted based on a height-for-age < −2 sd below the WHO reference median. Maternal overweight/obesity was defined as a BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 36 publications
6
16
0
1
Order By: Relevance
“…Low prevalence of child wasting (21%) compared to underweight and stunting might be the cause behind less occurrence of OBM/WC pairs [23]. The results are in accordance with other studies that reported DBM in Asia [48,49,53,54]. In the literature, it is well established that co-occurrence of under-and overnutrition is associated with nutrition transition [8].…”
Section: Plos Onesupporting
confidence: 87%
See 1 more Smart Citation
“…Low prevalence of child wasting (21%) compared to underweight and stunting might be the cause behind less occurrence of OBM/WC pairs [23]. The results are in accordance with other studies that reported DBM in Asia [48,49,53,54]. In the literature, it is well established that co-occurrence of under-and overnutrition is associated with nutrition transition [8].…”
Section: Plos Onesupporting
confidence: 87%
“…Among LMICs countries, the prevalence of DBM was 24.3% in Bangladesh [48], (16.3%) in Indonesia [53], (9.1%) in Myanmar [54], (8%) in China [55], (6.60%) in Nepal [49], and 3 (.9%) in Pakistan [47]. However, there are some methodological differences in conceptualising the MCDBM, but one thing is common that all these studies have taken mother-child pairs as…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we followed previous practice and classified DBM into the following 4 subtypes: (1) coexistence of maternal (paternal) overnutrition and child undernutrition, (2) coexistence of maternal (paternal) undernutrition and child overnutrition, (3) coexistence of maternal (paternal) overnutrition and child overnutrition, and (4) coexistence of maternal (paternal) undernutrition and child undernutrition. 3,7,20 We constructed dichotomous variables for DBM and all DBM subtypes, with 1 indicating the households confronting adverse health outcomes and 0 indicating otherwise. For children, overnutrition referred to a weight-for-age z score of more than 2 SDs; undernutrition referred to 1 or more of the following conditions: underweight (weight-for-age z score of <−2 SD), wasting (weightfor-height z score of <−2 SD), stunting (height-for-age z score of <−2 SD), or anemia (hemoglobin count <11 g/dL).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…In terms of studies on DBM, maternal education has often been included as a covariate, but the findings have been inconsistent. Some studies reported that higher maternal education was associated with a higher risk of DBM . A study in Myanmar found that households with mothers with primary education had 62% higher odds of experiencing DBM than those with no maternal education .…”
Section: Introductionmentioning
confidence: 99%
“…Our primary outcome was DBM, defined at child level as the coexistence of an undernourished child and an overweight/obese mother [24][25][26][27]. Data on the DBM were also decomposed into the two components of this definition, child undernutrition and maternal overweight/obesity, to highlight the different combinations and permutations of maternal and child nutritional status.…”
Section: Outcome Variablementioning
confidence: 99%